RANCANG BANGUN SISTEM INFORMASI ABSENSI DAN PENGGAJIAN SORTER PHL PADA PT PAXEL ALGORITA UNGGUL CABANG JAKARTA UTARA - Sata Lesmana; Hanny Pertiwi (POLITEKNIK LP3I JAKARTA, 2025)
An employee's discipline in a company can be seen and measured from their attendance rate at work, because attendance is one of the factors that determines a company's productivity. Supporting facilities are then built to support human resource management, particularly in terms of work productivity in the workplace. A supporting suggestion is a system that can detect employee attendance. This system was created using a classic system development pattern commonly known as SDLC (System Development Life Cycle), using the MVC (Model-View-Controller) method, with CodeIgniter framework software, and packaged in web form.